Sangyod rice bran extract enhances Lacticaseibacillus paracasei growth during the exponential phase and antibacterial activity of L. paracasei supernatant against zoonotic and foodborne pathogens - Krittika Kabploy; Phirabhat Saengsawang; Chonticha Romyasamit; Suthinee Sangkanu; Warangkana Kitpipit; Thotsapol Thomrongsuwannakij; Tuempong Wongtawan; Mareena Daus; Maria de Lourdes Pereira; Watcharapong Mitsuwan (Veterinary World, 2022)
Background and Aim: Prebiotics are a group of nutrients or compounds that are degraded by the gut microbiota, including Lacticaseibacillus paracasei. The probiotic plays an important role in adhesion to the gut and is able to produce antimicrobial substances to inhibit pathogens. This study aimed to investigate the effects of Sangyod rice bran extract on the growth promotion of L. paracasei. Furthermore, antibacterial activity of the extract and L. paracasei supernatants cultured in De Man, Rogosa and Sharpe (MRS) medium plus the extract against zoonotic and foodborne pathogens was investigated.